2011
DOI: 10.1007/s11703-011-1093-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of harvesting time on fruit quality and internal browning of ‘Wonhuwang’ pear during cold storage

Abstract: Average fruit weight, seed browning, flesh firmness, total soluble solids, internal browning, and skin blackening were used to determine the optimum harvesting time of 'Wonhuwang' pear. Pears for storage were picked three times at 5-day intervals before, during, and after estimated optimum harvesting date. Average fruit weight and seed browning degree were calculated at each picking time. Quality changes, internal browning, and skin blackening were employed to estimate the optimum harvest date. It was found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 7 publications
0
7
0
1
Order By: Relevance
“…The softening of flesh during cold storage could be due to the degradation of soluble pectin by high activity of endopolygalacturonase in fruits. Pears harvested earliest had the highest firmness both before and after storage and lost less percentage of their firmness during storage (Li et al 2011).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The softening of flesh during cold storage could be due to the degradation of soluble pectin by high activity of endopolygalacturonase in fruits. Pears harvested earliest had the highest firmness both before and after storage and lost less percentage of their firmness during storage (Li et al 2011).…”
Section: Resultsmentioning
confidence: 94%
“…However, on complete hydrolysis of starch, no further increase in TSS occurs and consequently a decline in TSS is predictable as they are the primary substrates for respiration and are used by fruits in various metabolic activities (Wills et al 1980). Li et al (2011) reported that the latest picked pears showed higher total soluble solids value and serious internal browning and skin blackening due to their over ripeness. Storage period and shelf life intervals did not significantly influenced the acid content in juice of pear fruits (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…The development of disorders during postharvest ripening and storage of fruit also depends on a range of preharvest factors such as climate conditions. Other factors that have been considered to be influencing the development of the disorder are the size/weight of the fruit and the picking date (Ho et al, 2010a;Lammertyn et al, 2000;Li et al, 2011). Over-mature (late picked) and large fruit have been shown to be more susceptible to core breakdown during storage (Franck et al, 2007;Lammertyn et al, 2000;Verlinden et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Development of internal browning during stone fruit storage depends on a range of factors such as fruit maturity (Bowen and Watkins, 1997;Li et al, 2011), temperature during the growing seasons (Ferguson et al, 1999;Sakuma, 2003;Zerbini et al, 2002), or temperature and carbon dioxide interaction (Watkins and Liu, 2010). Mineral nutrient distribution in developing fruits is the most frequently discussed cause of physiological disorders in post-harvest fruits, of which calcium (Ca) deficiency is the most common factor (Fallahi et al, 1997;Franck et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Browning disorders have been found in several Japanese pear cultivars (Cho et al, 2010;Lee et al, 2007;Li et al, 2011;Zhang et al, 2009;Zhou et al, 2008), and in a new Taiwanese cultivar 'Taichung No. 2'.…”
Section: Introductionmentioning
confidence: 99%